Assessing holistic agroecological resilience of agroecosystems from a landscape perspective: a systematic review - Paula Schatte; Markus A Meyer (Ecology and Society, 2025)
Agricultural landscapes generally fulfill partially contradictory objectives: ensuring agricultural production (social and economic interests) and providing ecosystem functions (ecological interests). On one hand, maximizing production has led to highly intensive agricultural management. On the other hand, this intensification has caused numerous changes in key aspects of agricultural systems that likely affected the resilience, in particular loss of (agro)biodiversity, loss of landscape heterogeneity, loss of social diversity (fewer farmers, less knowledge), and sharp decline in ecosystem services. The concept of agroecological resilience considers the capacity of the holistic agroecosystem (including practical, social, and economic aspects) to respond continuously and dynamically to external and internal disturbances, such as drought and landscape-related management. Agroecological resilience therefore has the potential to consider interdependencies between humans and ecosystems and provide transformation paths in view of today’s obstacles in agricultural production. To develop an approach for a holistic assessment of resilience in agroecosystems, we did a comprehensive literature search on recently published assessments of agroecological resilience. The systematically reviewed studies (n = 42) were classified into two clusters using a hierarchical cluster analysis. The first cluster represents quantitative modeling approaches combined with case studies and GIS-based or remote-sensing-based spatial analysis (quantitative cluster). The second cluster represents qualitative approaches (e.g., questionnaires, interviews) in combination with case-study approaches (qualitative cluster). The quantitative studies, modeling agricultural landscapes for a representation of agroecological resilience, could include a greater representation of social aspects (e.g., stakeholder opinion on management decisions). Qualitative studies, on the other hand, assessed agroecological resilience more holistically, in particular by including social resilience. Generally, robustness was frequently studied in contrast to transformability and adaptability. Overall, our study calls for combining quantitative modeling with qualitative assessment of local stakeholders’ needs. This allows for assessing agroecological resilience holistically by taking into account locally driven social factors and may initiate a research-led transformation process toward more resilient agroecosystems.